Murine In vitro Memory T Cell Differentiation - Kim, Myoungjoo V. (Bio Protoc, 2014)
Upon pathogen encounter, naïve CD8(+) T cells are primed and undergo massive clonal expansion. A fraction of effector CD8(+) T cells remains during the contraction phase and differentiate into memory T cells critical for mounting robust recall responses in response to secondary infection. Low frequency of memory T cells in vivo is a major obstacle to investigate their functional aspects including migration capacity and genetic regulation. Here, we describe detailed protocol for memory T cell differentiation developed by von Andrian’s group to generate large number of CD44(hi)CD62L(hi) antigen-specific memory T cells in vitro.